2020
DOI: 10.1089/jwh.2019.7766
|View full text |Cite
|
Sign up to set email alerts
|

#MedToo: A Large-Scale Examination of the Incidence and Impact of Sexual Harassment of Physicians and Other Faculty at an Academic Medical Center

Abstract: Background: A landmark National Academies report highlighted the need for rigorous evaluation of sexual harassment in medicine. We examined the prevalence and impact of sexual harassment using the Sexual Experiences Questionnaire, the standard for measurement of sexual harassment, but which has not been previously applied within academic medicine. Materials and Methods: A 20-minute online survey was administered to all faculty who had been working at University of Michigan Medical School for at least 1 year (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
124
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 32 publications
11
124
0
1
Order By: Relevance
“…The authors’ findings are consistent with previous studies of sexual harassment. Although estimates vary, sexual harassment is highly prevalent 2. Other studies have identified serious physical and mental health sequelae of sexual harassment 34.…”
mentioning
confidence: 99%
“…The authors’ findings are consistent with previous studies of sexual harassment. Although estimates vary, sexual harassment is highly prevalent 2. Other studies have identified serious physical and mental health sequelae of sexual harassment 34.…”
mentioning
confidence: 99%
“…Another study by Vargas et al examined incidences and Impacts of Sexual Harassment of Physicians and other Faculty at an Academic Medical Center. The study revealed that increased harassment experiences were independently associated with lower mental health, job satisfaction, a sense of safety at work, and increased turnover intentions, with no significant interactions by gender (Vargas et al 2020). Another study entitled Sexual Harassment in Law Enforcement Incidence, Impact, and Perception found that general job stress, frustration, trauma outside of the workplace, were the ill effects of harassment (Lonsway, Paynich & Hall, 2013).…”
Section: Source: Compilation Of Secondary Datamentioning
confidence: 99%
“…Although the consequences of trauma are well studied, 9 we lack the same depth of information about the specific consequences of sexual harassment. 10 Vargas et al 3 report an association of lower mental health, job satisfaction, and feeling of safety at work with sexual harassment in both female and male participants. A cross-sectional study will not allow establishing causality, but these associations and patterns are recurring.…”
mentioning
confidence: 99%
“…If 60%-80% of the workforce is affected, the perpetrators cannot be few. Second, if employees are explicitly asked about the identity of perpetrators, insiders are most frequently mentioned, in Vargas et al 3 and other studies 6 with the only exception of emergency rooms. 7 It is important to acknowledge patients and their families as perpetrators, 8 but the main source of harassment are insiders, colleagues, and superiors.…”
mentioning
confidence: 99%